Surveillance farm: Towards a research agenda on Big Data agriculture - Klauser, Francisco (My University, 2018)
Farming today relies on ever-increasing forms of data gathering, transfer, and analysis. Think of autonomous tractors and weeding robots, chip-implanted animals and underground infrastructures with inbuilt sensors, and drones or satellites offering image analysis from the air. Despite this evolution, however, the social sciences have almost completely overlooked the resulting problematics of power and control. This piece offers an initial review of the main surveillance issues surrounding the problematic of smart farming, with a view to outlining a broader research agenda into the making, functioning, and acting of Big Data in the agricultural sector. For surveillance studies, the objective is also to move beyond the predominant focus on urban space that characterises critical contemporary engagements with Big Data. Smart technologies shape the rural just as much as the urban, and “smart farms” are just as fashionable as “smart cities.”